Urbach’s edge of glassy HgSe-GeSe₂ alloys: static disorder and temperature dependence of optical absorption - Bozhko, V.V.; Halyan, V.V.; Parasyuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Results of investigations of spectral characteristics in the fundamental absorption range for the glass-like alloys HgSe - GeSe₂ are represented. To explain the phenomenon of anomaly growth of the static disorder, the model of deforming tensions is discussed. The hypothesis concerning a sharp change of physical-and-chemical properties for the transition over the double eutectic point on the stable phase diagram of the HgSe - GeSe₂ system with a changing glass-creating matrix is suggested.